2004
DOI: 10.2355/isijinternational.44.294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduction Conditions on the Swelling Behaviour of Cement-bonded Briquettes

Abstract: Cement-bonded agglomerates of by-products generated in iron and steel plants are commonly used as burden material for blast furnaces. It has been observed that under certain conditions the briquettes containing pellet-fines show a tendency to swell catastrophically when reduced at 900-1 000°C using carbon monoxide as reducing agent. This swelling is dependent upon a number of factors like: reducing temperature, reducing conditions and composition of reducing gas. The optical micrographs do not show the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 5 publications
2
33
0
Order By: Relevance
“…Swelling can be categorized into normal swelling, up to 20% in volume, [1][2][3][4][5] and abnormal, i.e. catastrophic swelling, which may exceed 400% in volume at worst.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Swelling can be categorized into normal swelling, up to 20% in volume, [1][2][3][4][5] and abnormal, i.e. catastrophic swelling, which may exceed 400% in volume at worst.…”
Section: Introductionmentioning
confidence: 99%
“…Normal swelling up to 20 vol-% occurs during the transformation of the pellets from hematite to magnetite in the initial stages of reduction, in which the crystal structure changes from hexagonal to cubic. 2,7,8) Singh and Björkman 2) state that conversion from magnetite to wüstite can also lead to swelling to some extent. Abnormal swelling occurs during the transformation of wüstite to metallic iron in the latter stages of reduction and is generally believed to be caused by the growth of iron whiskers in the reduction of wüstite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4) Maneesh et al 5,6) studied the effect of reduction conditions on the swelling behavior of cement bonded briquettes. They found that the swelling of briquettes increases with the increase in average particle size of the raw material also the briquettes containing a larger amount of slag-forming oxides, CaO, SiO 2 , MgO and Al 2 O 3 may swell more.…”
Section: Introductionmentioning
confidence: 99%